2021
DOI: 10.1021/acs.jpclett.0c03394
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Defect-Related Luminescence in a Eu2+-Doped Chlorosilicate Phosphor

Abstract: Defects play non-negligible roles in many luminescent processes, where the significant and remarkable influence in the phosphor performance in various ways is observed. A full and clear perception of defects would be beneficial for the further development of the luminescence mechanism and design of phosphors. In this study, the defect-related luminescence in a chlorosilicate phosphor Ca 2 SiO 3 Cl 2 : Eu 2+ was deeply studied. Except for the green emission originating from the d−f transition of the Eu 2+ ion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…Using the XPS results, it is shown that both Eu 2+ and Eu 3+ existed in the studied samples by substituting Sr 2+ . When Sr 2+ was replaced by Eu 2+ , the coordination situation altered, resulting in the formation of an defect, 31 in which the strontium vacancy (V′′ Sr ) was formed to maintain the charge balance. Furthermore, as for the substitution of Sr 2+ by Eu 3+ , the positive point defect was generated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the XPS results, it is shown that both Eu 2+ and Eu 3+ existed in the studied samples by substituting Sr 2+ . When Sr 2+ was replaced by Eu 2+ , the coordination situation altered, resulting in the formation of an defect, 31 in which the strontium vacancy (V′′ Sr ) was formed to maintain the charge balance. Furthermore, as for the substitution of Sr 2+ by Eu 3+ , the positive point defect was generated.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, because the designed samples were prepared in a reducing atmosphere, the oxygen vacancy and the chlorine vacancy inevitably exist in the final products. 31 Because of the occurrence of these defects, they have the capacity of harvesting incident electrons, which cannot be escaped at room temperature because of the high trap depth, under NUV light excitation. Nevertheless, as the temperature increased, electrons could obtain enough energy to escape from the defect levels and populate the 5d level of Eu 2+ , and then participate in the radiative transition of Eu 2+ , as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[74] The trap depth E T is calculated by Urbach method: E T = T m /500, where T m is peak temperature. [75] The estimated trap depths for these four glow peaks are 0.678, 0.738, 0.848, and 1.026 eV, respectively. The PL intensity of CaGa 2 O 4 :Bi 3+ under UV light excitation gradually increases with the increase of ambient temperature.…”
Section: Defect Engineeringmentioning
confidence: 95%